UK Medical Cannabis registry: an analysis of clinical outcomes of medicinal cannabis therapy for chronic pain conditions. Issue 4 (3rd April 2022) - Harris, Michael; Erridge, Simon; Ergisi, Mehmet; Nimalan, Devaki; Kawka, Michal; Salazar, Oliver; Ali, Rayyan; Loupasaki, Katerina; Holvey, Carl; Coomber, Ross; Usmani, Azfer; Sajad, Mohammed; et al.
ABSTRACT: Objectives: To explore pain-specific, general health-related quality of life (HRQoL), and safety outcomes of chronic pain patients prescribed cannabis-based medicinal products (CBMPs). Methods: A case series was performed using patients with chronic pain from the UK Medical Cannabis Registry. Primary outcomes were changes in Brief Pain Inventory short-form (BPI), Short-form McGill Pain Questionnaire-2 (SF-MPQ-2), Visual Analogue Scale-Pain (VAS), General Anxiety Disorder-7 (GAD-7), Sleep Quality Scale (SQS), and EQ-5D-5L, at 1, 3, and 6 months from baseline. Statistical significance was defined at p-value<0.050. Results: 190 patients were included. Median initial Δ 9 -tetrahydrocannabinol and cannabidiol daily doses were 2.0mg (range:0.0–442.0mg) and 20.0mg (range:0.0–188.0mg) respectively. Significant improvements were observed within BPI, SF-MPQ-2, GAD-7, SQS, EQ-5D-5 L index, and VAS measures at all timepoints (p<0.050). Seventy-five adverse events (39.47%) were reported, of which 37 (19.47%) were rated as mild, 23 (12.11%) as moderate, and 14 (7.37%) as severe. Nausea (n=11; 5.8%) was the most frequent adverse event. Conclusion: An association was identified between patients with chronic pain prescribed CBMPs and improvements in pain-specific and general HRQoL outcomes. Most adverse events were mild to moderate in severity, indicating CBMPs were well tolerated. Inherent limitations of study design limit its overall applicability.